Analysis of Sharia Marketing Strategy on Bt Batik Trusmi Business - Syamsul Huda; Anik Yuliati (Eduvest - Journal of Universal Studies, 2022)
The purpose of this study was to determine the marketing of BT Batik Trusmi in Trusmi Village, Cirebon. To find out the sharia marketing strategy at BT Batik Trusmi in Trusmi Village, Cirebon. To find out what are the obstacles to sharia marketing and their solutions. The research method used in this research is qualitative research in the form of case studies. The result of this research is that marketing at BT Batik Trusmi Cirebon when the sharia marketing strategy has not been implemented is to use conventional marketing like other shops so that the income is the same as other shops and even competes. The sharia marketing strategy implemented at BT Batik Trusmi Cirebon is by providing excellent service, such as: When the shop is about to close or a holiday is always given advance notice. The shop assistants always provide excellent service by being friendly and ready to provide the best service according to the 7S concept, namely: Greetings, Smiles, Greetings, Polite, Polite, Ready and Alert. The things that become obstacles in the sharia marketing strategy at BT Batik Trusmi Cirebon are: the community does not accept it with shops that often close due to prayer times, the difficulty in educating and teaching employees to always provide excellent service to customers. While the solutions to deal with these obstacles are: the surrounding community needs to be given understanding and habituation to be able to understand and accept that shops that implement Islamic marketing strategies will imitate the trade practiced by the Prophet, one of which is by closing the shop when prayer time arrives. Employees must be given training or upgrading every week to always provide excellent service to customers, Be more careful and updated in analyzing market prices so that they can provide the best prices and in accordance with the quality of goods, once a picnic is held so that employees do not get bored in serving customers, give understanding to consumers that the price is in accordance with the quality of the goods.